ANALISIS VALUASI SAHAM BANK DIGITAL DALAM PENGAMBILAN KEPUTUSAN INVESTASI DI BURSA EFEK INDONESIA - Akhmad . Yadi; Basuki Basuki; Rahmi Widyanti (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2026)
Stocks are a high-risk investing option. One of the key elements of investing is stock valuation. Stock valuation aims to reduce stock investment risk by determining intrinsic value for the purpose of making investment decisions. This type of research is descriptive quantitative and shares of digital bank issuers listed on the Indonesia Stock Exchange served as the research object. Free Cash Flow to Equity (FCFE) and Price to Book Value (PBV) are the two methods used to value stocks in this research. The data used are secondary data in the form of financial statements. Using a purposive sampling technique, the sample for this study consists of 5 shares of digital bank issuers. The FCFE method revealed that four stocks were overvalued and one stock was undervalued. Meanwhile, the PBV method revealed that one stock was overvalued stock and four stocks were undervalued. Based on these findings, an investment decision can be made to buy or hold shares that are undervalued and sell shares that are overvalued.